Perspectives of developing Halal-MICE tourism in Bukhara based on establishing the Bukhara Bureau of Convention and Exhibition (BBCE). - Kuvandikov Aziz Ravshanovich (Peerian Journals Publishing, 2023)
Bukhara, which is situated on the Silk Route, is more than 2,000 years old. It is the most complete example of a medieval city in Central Asia, with an urban fabric that has remained largely intact. Monuments of particular interest include the famous tomb of Ismail Samani, a masterpiece of 10th-century Muslim architecture, and a large number of 17th-century madrasas. .The Historic Centre of Bukhara, situated on the Silk Roads, is more than two thousand years old. It is one of the best examples of well preserved Islamic cities of Central Asia of the 10th to 17th centuries, with an urban fabric that has remained largely intact. Bukhara was long an important economic and cultural center in Central Asia.
Keywords: Bukhara city on Silk Road; Uzbekistan Chamber of commerce and industry; Development Strategy of New Uzbekistan